2016
DOI: 10.1016/j.colsurfa.2015.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Capillary rise dynamics of liquid hydrocarbons in mesoporous silica as explored by gravimetry, optical and neutron imaging: Nano-rheology and determination of pore size distributions from the shape of imbibition fronts

Abstract: We present combined gravimetrical, optical, and neutron imaging measurements of the capillarity-driven infiltration of mesoporous silica glass (Vycor) by hydrocarbons. Square-root-of-time Lucas-Washburn invasion kinetics are found for linear alkanes from n-decane (C10) to n-hexacontane (C60) and for squalane, a branched alkane, in porous monoliths with 6.5 nm or 10 nm mean pore diameter, respectively. Humiditydependent experiments allow us to study the influence on the imbibition kinetics of water layers adsor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 170 publications
(221 reference statements)
6
57
0
Order By: Relevance
“…The two types will be termed V5 (r 0 = 3.4 nm, φ 0 =0.315±0.005) and V10 (r 0 = 5.0 nm, φ 0 =0.3±0.005) in the following. The characterization of the matrix properties, in particular r 0 , relies on volumetric nitrogen sorption isotherms performed at 77 K. [48] The relatively low porosity along with the high elastic modulus of the silica glass renders any liquid-uptake-induced mechanical deformation negligible [66], in the sub-percent range. Any impact of swelling or contraction, which in principle could affect the imbibition process significantly [67] can thus be ignored.…”
Section: Porous Glass Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…The two types will be termed V5 (r 0 = 3.4 nm, φ 0 =0.315±0.005) and V10 (r 0 = 5.0 nm, φ 0 =0.3±0.005) in the following. The characterization of the matrix properties, in particular r 0 , relies on volumetric nitrogen sorption isotherms performed at 77 K. [48] The relatively low porosity along with the high elastic modulus of the silica glass renders any liquid-uptake-induced mechanical deformation negligible [66], in the sub-percent range. Any impact of swelling or contraction, which in principle could affect the imbibition process significantly [67] can thus be ignored.…”
Section: Porous Glass Substratesmentioning
confidence: 99%
“…In the following we outline a phenomenological treatment of the capillary rise in a porous medium, as described in detail in Refs. [48] [68]. It assumes that both gravitational and inertial affects are negligible compared to the huge capillary forces in the nanopores.…”
Section: Darcy Analysis Of Liquid Imbibition In a Hydrophilic Nanopormentioning
confidence: 99%
See 1 more Smart Citation
“…(11) and dropping the asterisks, the following dimensionless equation is obtained for the capillary filling dynamics: (13) where and .…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Tas et al [8] and Persson et al [9] reported a smaller rate of filling of glass nanochannels by de-ionized water compared to an uncharged capillary condition, which might be attributed to the retarding electrical effect of the capillary wall. Gruener et al [10,11] attributed the reduced filling kinetics in nanochannels compared to the classical Lucas-Washburn prediction to the adsorbed, immobile layers at channels or pore walls.…”
Section: Introductionmentioning
confidence: 97%